PS47 Could Improved Training Opportunities Reduce Health Workforce Migration From Sub-Saharan Africa? Evidence From A Discrete Choice Experiment Among Pharmacists. (17th September 2012) - Stynes, G; Oketch, M; Smith, F; Smith, R; Owusu-Daaku, R; Lagarde, M
Abstract : Background: Sub-Saharan Africa (SSA) suffers from acute shortages of all types of health workers, partly due to high rates of health workforce migration (HWM) to high-income countries. The role of non-financial incentives in HWM is inadequately defined and their potential as policy levers is overlooked. This study examined the hypothesis that improved local education opportunities could alter the relative uptakes of local and foreign training, ultimately reducing education-led HWM from SSA. Initial qualitative research (reported separately) found that SSA pharmacists valued seven key education-related factors: location (SSA or elsewhere), cost, availability of their preferred course, learning approach (theoretical or practical), course length, access to learning resources (e.g. equipment) and institutional quality. Methods: A discrete choice experiment (DCE) was designed to enable quantification of the relative influence of these attributes on SSA pharmacists' education location decisions. Convenience and snowball sampling strategies were necessary, due to limited resources and incomplete sample frames. Participants self-administered a paper- or web-based DCE, comprising 16 labelled choice sets. Each choice set consisted of three hypothetical alternatives: a nominally SSA-based education opportunity (encompassing some split-site programmes with varying proportions of time spent abroad); a fully foreign-based education opportunity; and a 'delayed choice' option. Hypothetical alternatives were differentiated in each choice set, by varying the levels of the seven education attributes, which represented current and prospective standards for each attribute. Respondents chose one alternative per choice set. The resulting choice data were modelled using the mixed logit model, taking into account respondents' socio-demographic characteristics and varying preferences. Results: 428 practising pharmacists and pharmacy students, of SSA origin and any migration status, were recruited in Ghana (face-to-face), the UK and online (both via email). Approximately one-third of respondents displayed unvarying, dominant preferences for one education alternative, regardless of variations in the seven attributes. The preferred alternative in this group was usually the education alternative located fully overseas. Nevertheless, two-thirds of respondents were willing to make at least one trade-off between different levels of different attributes, i.e. the majority of respondents chose the local alternative and the overseas alternative at least once each. Conclusion: The results are intended to inform policymakers seeking new and sustainable ways to address the crisis of HWM in low-income countries. These findings offer hope that a non-trivial proportion of health workers, who migrate to pursue education abroad, might be persuaded to study at home if policymakers implemented desirable changes to local education opportunities.